Increasing Coconut Sap Production With Liquid Organic Fertilizer Application In Dry Season - Taufik Budhi Pramono; Purwanto - - (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
The objective of this research was to asses the effect of organic liquid fertilizer application in shoot of coconut plant to coconut sap production. This research was held in Candinata Village, Kutasari Distric, Purbalingga District in August 2015. The treatments were application of organic liquid fertilizer, and without application of organic liquid fertilizer. The data was collected one week after treatment application until three weeks respectively. The observed variables were volume of coconut sap production per day, pH, and sugar brix content. The result of this research showed that organic liquid fertilizer application in shoot of coconut plant increase the coconut sap production (10,89%) and sugar brix (one point) in dry season.